Kontribusi Sosial Muhammadiyah: Dari Teologi ke Aksi Nyata - Fathony, Bimba Valid; Permadi, Indra; Pambudi, Muhammad Sidiq (Pelita: Jurnal Studi Islam Mahasiswa UII Dalwa, 2025)
Muhammadiyah, at its inception, was a religious organization that sought to provide answers to the problems faced by the community at that time. Al-Ma'un Theology is a concept initiated by KH. Ahmad Dahlan, the spirit of the Al-Ma'un letter became Muhammadiyah's support in carrying out social transformation as a form of implementing "Progressive Islam". This type of research is included in the library research category, where the object of study uses data sources from literature. In the research entitled "Muhammadiyah's Social Contribution: From Theology to Real Action" the researcher concluded that Al-Ma'un Theology plays a role as a social, humanitarian, and liberation theology, which emphasizes real action rather than merely classical theological discourse. This makes religion a force that drives social development and societal change. Al-Ma'un Theology functions as a social foundation that integrates religious values with real social action. Muhammadiyah's Amal Usaha (AUM) is a concrete form of action from the Muhammadiyah da'wah movement which acts as a medium for the concrete implementation of Islamic values in various areas of community life. Muhammadiyah responds to contemporary social issues by adopting educational approaches, social services, and religious fatwas that are relevant to the times to respond to current social, cultural, and technological challenges.